Physicochemical and photocatalytic properties of FE+3-Doped TiO2 nanotubes fabricated via hydrothermal process - Venezuela, Jeffrey dG (Philippine Engineering Journal)
Iron (III) doped TiO2 nanotubes were prepared by an impregnating-calcination method using the hydrothermally prepared titania nanotubes as precursors and Fe(NO3)3 as dopant. The samples were characterized by transmission electron microscope, x-ray diffraction and N2 adsorption-desorption isotherm. The photocatalytic activity was evaluated by the photocatalytic degradation of methyl orange under visible-light irradiation. Surface structure analysis showed that the nanotube morphology was created at hydrothermal treatments of 120°C. The nanotube structure was preserved even after the doping calcination step. X-ray diffractogram confirmed the presence of anatase and rutile in the processed titania. Surface area of the samples observed to increase with increasing concentration of dopant. The 1.0 percent Fe+3-doped sample exhibited the highest photocatalytic activity. The high photocatalytic property of the Fe+3 doped TiO2 powders could be diluted to the combined effects of Fe-doping, large specific area and small crystallite size.